2021
DOI: 10.7818/ecos.2175
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of forest loss in the southeast of the Peruvian Amazon: a case study in Madre de Dios

Abstract: : La Amazonia occidental, puntualmente la región de Madre de Dios, es conocida como la capital de la biodiversidad del Perú y es reconocida mundialmente como uno de los lugares con mayor biodiversidad de la Tierra. Sin embargo, se ha visto amenazada por un grave problema de pérdida de bosques. Las principales amenazas ambientales se deben a una mala gestión del territorio que ocasionan la concentración de tierras, expansión agrícola, ganadería, minería de oro y la explotación económica descontrolada. El presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 39 publications
1
21
0
2
Order By: Relevance
“…AGB strongly influences ecosystem processes [79] and tropical forests store significant quantities of AGB accumulated in woody plants [86]-64% of global forest AGB [87]. However, the expansion of deforestation and forest degradation in Madre de Dios persists [19,88], resulting in the emission of carbon into the atmosphere [16]. The mean AGB determined in 20-25 years of recovery, 198 ± 115 Mg ha −1 in areas of suction pumping mining and 45 ± 78 Mg ha −1 in areas recovering from heavy machinery mining in this study is less than the mean AGB reported for tropical Amazon forest from Madre de Dios (230-450 Mg ha −1 ) [39,86,89].…”
Section: Recovery Of Agb Tree Diversity and Forest Structurementioning
confidence: 99%
See 2 more Smart Citations
“…AGB strongly influences ecosystem processes [79] and tropical forests store significant quantities of AGB accumulated in woody plants [86]-64% of global forest AGB [87]. However, the expansion of deforestation and forest degradation in Madre de Dios persists [19,88], resulting in the emission of carbon into the atmosphere [16]. The mean AGB determined in 20-25 years of recovery, 198 ± 115 Mg ha −1 in areas of suction pumping mining and 45 ± 78 Mg ha −1 in areas recovering from heavy machinery mining in this study is less than the mean AGB reported for tropical Amazon forest from Madre de Dios (230-450 Mg ha −1 ) [39,86,89].…”
Section: Recovery Of Agb Tree Diversity and Forest Structurementioning
confidence: 99%
“…Land use changes in tropical forests, however, are occurring at a faster rate than in other regions of the planet, and this imbalance between deforestation and forest restoration has serious effects on the global carbon cycle [18]. Agriculture and goldmining are the primary drivers of deforestation in the southern Peruvian Amazon [19], although mining activity causes the most severe impacts [20,21]. The resilience of these ecosystems after abandonment by mining activities remains to be studied in detail [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, the western Amazon is one of the most biologically and culturally diverse areas in the world, with a high diversity of flora, the largest number of mammal, bird, and amphibian species on the continent, and many indigenous cultures. Forest concessions and protected areas in Madre de Dios provide important economic benefits to the local population through nature-based tourism and NTFPs [2][3][4][5]. However, without proper planning, socioeconomic activities in tropical forests (such as logging and agriculture) endanger biological diversity [1]; this problem has worsened in Peruvian tropical forests in recent years, primarily as a result of gold mining [4,6] and agriculture [2].…”
Section: Introductionmentioning
confidence: 99%
“…Forest concessions and protected areas in Madre de Dios provide important economic benefits to the local population through nature-based tourism and NTFPs [2][3][4][5]. However, without proper planning, socioeconomic activities in tropical forests (such as logging and agriculture) endanger biological diversity [1]; this problem has worsened in Peruvian tropical forests in recent years, primarily as a result of gold mining [4,6] and agriculture [2].…”
Section: Introductionmentioning
confidence: 99%